Developing physical resilience strategies in passive defense according to identification of endangered areas of urban environments (case study: Ahvaz city). Issue 1 (2nd June 2021) - Pouryarmohammadi, Mozhdeh; Ahmadi, Hasan; Salaripour, AliAkbar
Abstract : Purpose: This paper aims to focus on reducing the vulnerability of Ahvaz city against urban disasters and lowering the number of casualties and amount of financial losses using modern approaches to develop resilience strategies that can increase urban safety to an acceptable level. The strategic situation of Ahvaz city, because of its abundant resources, the war experience and its location on the boundary regions of Iran, highlights its significance. Ahvaz has a high population and an extended texture, and the existence of extraordinary constructions increases the importance of physical resilience in this city. Design/methodology/approach: The present study investigates built environment aspects such as the urban structure, the urban form, land-use proximity pattern, urban road network and crucial and vulnerable centres in Ahvaz, using a combination of qualitative and quantitative methods. Hence, the areas at risk in Ahvaz were identified and illustrated in a comprehensive risk assessment map, and then, by using the strengths, weaknesses, opportunities and threats technique and finally by using the Delphi method, some strategies and plans were presented to reduce the level of vulnerability in Ahvaz. Then, these strategies are prioritized by applying quality function deployment (QFD) technique. Findings: The risk assessment result shows that most parts of Ahvaz's urban areas are highly at risk. The central and northern parts of Ahvaz have the highest vulnerability at a time of crisis. These zones include district 1 (city centre) and districts 2, 3 and 7 at the city's margins. The result of QFD process showed that the essential urban resilience strategy is to positively consider the passive defence studies with a physical resilience approach. Also, the proper distribution of strategic points in the city, moving the industrial and oil companies from the peripheral area, and facilitating access to vital, crucial centres to support urban regions are considered the most effective strategic plans. Originality/value: This paper, with an integrated approach, examines and prioritizes the main physical problems of Ahvaz city based on the spatial analysis and opinions of experts. The physical strategies presented in this paper can significantly reduce the risks and increase the urban resilience of Ahvaz city in the face of crisis.